The influence of motivation, work discipline, and work environment on employee performance at PT. Cipta Rasa Multindo - Alya, Nur; Febriyantoro, Mohamad Trio; Zulkifli, Zulkifli; Suleman, Dede; Saputra, Fendi; Suyoto, Yohanes Totok (Priviet Social Sciences Journal, 2022)
This study aims to examine and analyze the effect of motivation, work discipline, and work environment on employee performance. The object of research in this writing is the employees of PT. Cipta Rasa Multindo. Respondents in this study amounted to 40 employees with the criteria of respondents aged 20-40 years. Data collection techniques using survey methods through questionnaires. The results of this study resulted in the finding that the variable motivation has a negative and not significant effect on employee performance, work discipline has a negative and significant effect on employee performance and the work environment has a positive and significant effect on employee performance.